Validating a critical thinking scale: an essential skill for vocational education students in the era of artificial intelligence - Eva María Olmedo-Moreno; José Javier Romero-Díaz de la Guardia; Jorge Expósito-López; Ramón Chacón-Cuberos; Noelia Parejo-Jiménez (Institute of Advanced Engineering and Science, 2026)
Critical thinking is a fundamental competence in education and professional training, particularly in a technology-driven era increasingly shaped by generative artificial intelligence (GenAI). To address the need for contextually relevant assessment tools, this study aimed to evaluate the reliability and validity of the critical thinking disposition scale (CTDS) among vocational training (VT) students. A descriptive, exploratory, and cross-sectional design was applied using quantitative methods. Data was collected from 879 students enrolled in VT programs. Exploratory and confirmatory factor analyses were conducted to examine the scale’s factorial structure, reliability, and construct validity. Results supported an 11-item structure comprising two dimensions—executive function and reflective thinking—with satisfactory psychometric properties (KMO=0.817; CFI=0.883; TLI=0.851; RMSEA=0.0672; SRMR=0.0428). The findings confirm that the CTDS is a reliable and valid instrument for assessing critical thinking dispositions in vocational education. This tool provides educators and researchers with a robust means to evaluate critical thinking, a key competence for learning, personal development, and professional preparedness in the age of GenAI. This is the first validation of the CTDS with VT students in Spain.